Uterine smooth muscle tumor analysis by comparative genomic hybridization: a useful diagnostic tool in challenging lesions - Croce, Sabrina; Ribeiro, Agnes; Brulard, Celine; Noel, Jean-Christophe; Amant, Frederic; Stoeckle, Eberhard; Devouassoux-Shisheborah, Mojgan; Floquet, Anne; Arnould, Laurent; Guyon, Frederic; Mishellany, Florence; Garbay, Delphine; et al. (Modern pathology, 2015)
The diagnosis and management of uterine smooth muscle tumors with uncertain malignant potential (STUMP) is often challenging, and genomic data on these lesions as well as on uterine smooth muscle lesions are limited. We tested the hypothesis that genomic profile determination by array-CGH could split STUMP into a benign group with scarce chromosomal alterations akin to leiomyoma and a malignant group with high chromosomal instability akin to leiomyosarcoma. Array-CGH genomic profile analysis was conducted for a series of 29 cases of uterine STUMP. A group of ten uterine leiomyomas and ten uterine leiomyosarcomas served as controls. The mean age was 50 years (range, 24-85) and the follow-up ranged from 12 to 156 months (average 70 months). Since STUMP is a heterogenous group of tumors with genomic profiles that can harbor few to many chromosomal alterations, we compared genomic indices in leiomyomas and leiomyosarcomas and set a genomic index=10 threshold. Tumors with a genomic index <10 were classified as nonrecurring STUMPs and those with a genomic index >10 represented STUMPs with recurrences and unfavorable outcomes. Hence, the genomic index threshold splits the STUMP category into two groups of tumors with different outcomes: a group comparable to leiomyomas and another similar to leiomyosarcomas, but more indolent. In our STUMP series, genomic analysis by array-CGH is an innovative diagnostic tool for problematic smooth muscle uterine lesions, complementary to the morphological evaluation approach. We provide an improved classification method for distinguishing truly malignant tumors from benign lesions within the category of STUMP, especially those with equivocal morphological features.
Keywords: senioři; leiomyom; srovnávací genomová hybridizace; senioři nad 80 let; nádor z hladké svalové tkáně; Uterine Neoplasms; Leiomyoma; Middle Aged; Smooth Muscle Tumor; Comparative Genomic Hybridization; Neoplasm Recurrence, Local; Adult; mladý dospělý; lokální recidiva nádoru; Aged, 80 and over; Young Adult; ženské pohlaví; nádory dělohy; Humans; lidé středního věku; dospělí; Female; Aged; lidé